Hobgoblins, low-country Sinhalese plotters, or local elite chauvinists?:directions and patterns in the 1915 communal riots - Roberts, M. (My University, 1981)
Abstract available from Library, Please quote title when requesting
Keywords: Ethnicity; Social status; Communal riots; Social sciences